2023
DOI: 10.3389/fonc.2022.1100350
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of preoperative MRI features in the diagnosis of meningioma WHO grade and brain invasion

Abstract: ObjectiveThe preoperative MRI scans of meningiomas were analyzed based on the 2021 World Health Organization (WHO) Central Nervous System (CNS) Guidelines, and the efficacy of MRI features in diagnosing WHO grades and brain invasion was analyzed.Materials and methodsThe data of 675 patients with meningioma who underwent MRI in our hospital from 2006 to 2022, including 108 with brain invasion, were retrospectively analyzed. Referring to the WHO Guidelines for the Classification of Central Nervous System Tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The reason for this is that the new, revised criteria include BI as an independent, histological criterion for diagnosing AM. Formerly WHO grade 1 meningioma patients were included as having AM once the new BI-based criterion was applied to them, resulting in an increase of 1–10% in the incidence of AM [ 23 , 34 ], as well as an increase in the proportion of BI in AM. In terms of clinical risk factors for BI in AM, our study found that patient sex, age, tumor location, and V Tumor were not involved, consistent with the findings of several studies [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that the new, revised criteria include BI as an independent, histological criterion for diagnosing AM. Formerly WHO grade 1 meningioma patients were included as having AM once the new BI-based criterion was applied to them, resulting in an increase of 1–10% in the incidence of AM [ 23 , 34 ], as well as an increase in the proportion of BI in AM. In terms of clinical risk factors for BI in AM, our study found that patient sex, age, tumor location, and V Tumor were not involved, consistent with the findings of several studies [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies explored the correlation between BI and imaging features, such as peritumoral edema (PE), enhanced heterogeneity and irregular tumor shape, which were the independent risk predictors of BI [ 19 23 ]. Radiomics is an emerging image processing method developed in recent years that allows high-throughput extraction and quantitative analysis of radiomics features in images that cannot be identified by the naked eye [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several suggestive radiographic features that may be used to differentiate high-grade from benign meningiomas, including a lower apparent diffusion coefficient (reflecting higher cellularity), the radiographic sign of “mushrooming”, and high signal intensity on fluid-attenuated inversion recovery (FLAIR) sequences. A definitive pathological grade, however, cannot be established radiographically [ 4 , 5 ].…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…In einer aktuellen retrospektiven Studie von 675 Patienten mit einem Meningeom fanden sich 108 Fälle mit Hirninvasion des Tumors. Dabei konnten statistisch das Ausmaß des peritumoralen Ödems, die Größe des Tumors und niedrige ADC-Werte als unabhängige Prädiktoren für die Wahrscheinlichkeit des Nachweises einer Hirninvasion ermittelt werden [19].…”
Section: Meningeomeunclassified